2018
DOI: 10.1002/cncr.31649
|View full text |Cite
|
Sign up to set email alerts
|

Irrational fear of whole‐brain radiotherapy: Are we doing our patients a disservice?

Abstract: A previously healthy woman aged 64 years presents with persistent cough has a left hilar mass identified. Biopsy reveals adenocarcinoma without epidermal growth factor receptor mutation or anaplastic lymphoma kinase translocation. A right adrenal gland metastasis is identified on a positron emission tomography scan. Screening brain magnetic resonance imaging reveals multiple, enhancing masses consistent with metastatic disease. Over 40 areas of abnormal enhancement are noted within both cerebral hemispheres an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Stereotactic radiosurgery (SRS), which is defined as the delivery of a large conformal dose of radiation in 1 to 5 fractions to an intracranial target, has demonstrated excellent rates of local control (LC) and is associated with decreased cognitive side effects in comparison with whole‐brain radiation therapy (WBRT) 19‐29 . A concerning complication of SRS is radiation necrosis (RN), which has been observed in approximately 5% to 26% of patients, and is associated with increasing volumes of irradiated brain during SRS, particularly when the volume of brain tissue receiving a dose of 12 Gy or higher (V12 Gy) is > 8.5 to 10 cm 3 28,30‐39 .…”
Section: Introductionmentioning
confidence: 99%
“…Stereotactic radiosurgery (SRS), which is defined as the delivery of a large conformal dose of radiation in 1 to 5 fractions to an intracranial target, has demonstrated excellent rates of local control (LC) and is associated with decreased cognitive side effects in comparison with whole‐brain radiation therapy (WBRT) 19‐29 . A concerning complication of SRS is radiation necrosis (RN), which has been observed in approximately 5% to 26% of patients, and is associated with increasing volumes of irradiated brain during SRS, particularly when the volume of brain tissue receiving a dose of 12 Gy or higher (V12 Gy) is > 8.5 to 10 cm 3 28,30‐39 .…”
Section: Introductionmentioning
confidence: 99%
“…This is best illustrated in the treatment of limited brain metastases. Traditional approaches, such as whole brain radiation therapy (WBRT), while associated with excellent rates of tumor control, require 3–4 weeks of treatment and are associated with a significant risk of cognitive sequelae [ 17 , 92 , 93 , 94 , 95 ]. SRS has demonstrated excellent rates of tumor control with markedly decreased rates of cognitive sequelae and is now widely used in this setting [ 15 , 16 , 17 , 96 ].…”
Section: Stereotactic Radiosurgerymentioning
confidence: 99%
“…While WBRT is associated with excellent rates of local and regional brain control, it is also associated with significant rates of cognitive deterioration following treatment ( 13 15 , 73 76 ). Multiple studies have suggested that there is an association between cognitive functioning and quality of life ( 77 , 78 ).…”
Section: Brain Metastasesmentioning
confidence: 99%